Analisis Konseptual Pembelajaran Student Oriented pada Kurikulum Merdeka - Fathonah, Naila Izzatun; Anisa, Anisa; Naufal, Muhammad; Wianda, Muhammad Nabiel Augis; Abdurrahmansyah, Abdurrahmansyah (LPPPI Publishing, 2025)
This conceptual analysis explores the integration of student-oriented learning (SOL) within Indonesia’s Merdeka Curriculum, addressing the evolving needs of education in the post-pandemic era. The shift from traditional teacher-centered approaches to SOL is driven by the need to develop 21st-century skills critical thinking, collaboration, communication, and creativity amid rapid socio-economic changes and learning losses from COVID-19 disruptions. SOL empowers students as active agents in knowledge construction, with teachers acting as facilitators who tailor instruction to individual needs, motivations, and contexts. This aligns with the